(untitled) (Canadian Dermatology Today, 2021)
For medicine as a whole and especially for dermatology, few cultural shifts have had as monumental an effect as the rise of social media. It is quickly becoming evident in our clinical practices that with unprecedented access to reams of online information, clinicians are no longer the primary source of skin health information for patients. With social media platforms like YouTube, Instagram, and TikTok, patients can peruse millions of pieces of dermatology and skin-related content; overwhelmingly created by non-dermatologists, and of varying quality and accuracy. In order to understand and engage our patients, we must be aware of the information they consume and take part in the education process. It is now well-documented that social media has a significant influence on our patients’ treatment decisions. With over three billion active social media users worldwide, the sheer number of online platforms allow for unprecedented communication and spread of information. With the general public increasingly turning to social media for health information, many physicians are sharing information directly with the public, and dermatologists are among the group of physicians with a growing social media presence. However, with much of the skin-related content on social media created by non-dermatologists, it is important to consider why and how this media is consumed by patients, particularly given the recent rise in dermatology interest and content.